2018
DOI: 10.1371/journal.pone.0202246
|View full text |Cite
|
Sign up to set email alerts
|

How does nature exposure make people healthier?: Evidence for the role of impulsivity and expanded space perception

Abstract: Nature exposure has been linked to a plethora of health benefits, but the mechanism for this effect is not well understood. We conducted two studies to test a new model linking the health benefits of nature exposure to reduced impulsivity in decision-making (as measured by delay discounting) via psychologically expanding space perception. In study 1 we collected a nationwide U.S. sample (n = 609) to determine whether nature exposure was predictive of health outcomes and whether impulsive decision-making mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 98 publications
4
42
1
2
Order By: Relevance
“…Evidence suggests that individuals respond in a more self-controlled way for ecological decisions related to air quality with exposure to natural as opposed to built environments (Berry et al, 2019). These results were associated with expanded space perception as previously shown (e.g., Repke et al, 2018). Although an initial foundation, this research still represents an area that has much opportunity for growth.…”
Section: Nature Exposure and Environmentally Relevant Decision-makingsupporting
confidence: 67%
See 2 more Smart Citations
“…Evidence suggests that individuals respond in a more self-controlled way for ecological decisions related to air quality with exposure to natural as opposed to built environments (Berry et al, 2019). These results were associated with expanded space perception as previously shown (e.g., Repke et al, 2018). Although an initial foundation, this research still represents an area that has much opportunity for growth.…”
Section: Nature Exposure and Environmentally Relevant Decision-makingsupporting
confidence: 67%
“…In a follow-up experiment, similar results were obtained when participants walked through either natural landscape environments or built landscape environments and then chose between receiving money now or in the future. Our lab has also shown that individuals visually exposed to natural environments exhibit more self-controlled decisions, while individuals exposed to built environments demonstrate more impulsive decisions in a monetary delay-discounting task (Berry et al, 2014; see Figure 1; Berry et al, 2015), and this effect may be related to expanded time and space perception (Berry et al, 2015;Repke et al, 2018).…”
Section: Nature Exposure Health and Health Related Decision-makingmentioning
confidence: 76%
See 1 more Smart Citation
“…In order to create the appropriate environment for such a development, nature is displayed to offer a "stronger, authentic sense of self or offering a new perspective of oneself within the world" [47]. Repke et al [49] have shown in their research how the positive impact of nature is to some extent motivated by the decrease in impulsive behavior and fast reckless decision-making. The same authors further discovered that these benefits (decreased impulsive decision-making that is thought to generate health improvements) occur in people due to and expansion of the space perception [49].…”
Section: Water Qualitymentioning
confidence: 99%
“…Repke et al [49] have shown in their research how the positive impact of nature is to some extent motivated by the decrease in impulsive behavior and fast reckless decision-making. The same authors further discovered that these benefits (decreased impulsive decision-making that is thought to generate health improvements) occur in people due to and expansion of the space perception [49]. These results are further confirmed by findings showing that having access to a garden was linked to important health benefits, especially mental health, and also to social and emotional positive outcomes [50].…”
Section: Water Qualitymentioning
confidence: 99%